N-of-1 trial of thymoquinone and vorinostat in a patient with sialidosis type 1. Issue 5 (8th May 2017) - Liang, Christina; Peach, D; Stark, Samantha; Fietz, Michael
Abstract : Objectives: Sialidosis type 1 is an autosomal recessive disorder causing neuraminidase deficiency, leading to sialic acids accumulation in tissues. Clinically, patients have cherry red spots, normal intelligence, and a progressive cerebellar ataxia, with intention myoclonus and tremor. Currently there is no disease-modifying treatment. Thymoquinone is an agonist of Neu 4 sialidase activity and a weak histone deacetylase inhibitor. Vorinostat is a more potent histone deacetylase inhibitor. It is unclear if these may have an effect on patients with sialidosis. Methods: A 31 year old caucasian man presenting with a mild ataxic syndrome was diagnosed with sialidosis type 1. After initial dose-finding over 3 months, he was commenced on 3 months on-vs-off cycles of oral thymoquinone between 0.5-2g daily. At 3 months intervals, he was assessed by the scale for the assessment and rating of ataxia (SARA), Archimedes spiral-drawing, balance tests and targeting exercises. Urinary oligosaccharides were assessed semi-quantitatively by thin-layer chromatography. Physiological parameters and routine blood tests were monitored. Results: There was a consistent reduction in the patient's urinary oligosaccharides after periods of being on thymoquinone from 0.5–2g/day, with gastrointestinal side effects reported at doses beyond 2 g/day. The summed time for balance tests showed a significant improvement in balance after periods on thymoquinone (p=0.047), while the SARA score and tests for dysmetria showed no significant change (p=0.34). There was no change from baseline in the urinary oligosaccharides after periods on vorinostat, with asymptomatic neutropenia noted at the standard 300 mg/day dose. Conclusions: There is a clear physiological effect of thymoquinone on this patient with sialidosis type 1, which is not evident with vorinostat. Thymoquinone at <2 g/day appeared safe but the clinical effect size over the short period of the trial on a minimally affected patient was small. A further pilot study into a larger patient cohort will be helpful.